The Biogeochemistry of Lantanides in Soils - Yu. N. Vodyanitskii; O. B. Rogova (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
The lithogenous minerals containing lantanides (Ln) are unsustainable within the zone of hypergenesis. Their dilution impoverish soils in terms of lantanides content, especially in humid regions. In conditions of neutral environmental pH in dry steppe zone, the lantanides loose their mobility, and, hence, become unavailable for plants. The lantanides are characterized by the high biochemical and biological activity. The physiologic impact of lantanides on plants is set. The separate parts of vascular plants accumulate lantanides in different degree. The difference may reach 100-fold level. For many plants the accumulation of lantanides occurs at the reverse order: roots > leaves > stalks > grain/fruits. Lantanides accumulators (such as brackens), promote their accumulation within the humus layer of soils. Fertilizers with lantanides are widely implemented in China. They powder seeds and implement top dressing in soils with lantanides deficit, i.e., with low bulk content and/or with low availability for plants. Although at moderate increasing of Ln concentration in solution, there is often observed the increasing of the crop yield in laboratory conditions. However, the implementation of lantanides in the soil does not always give the positive effect. The main share of Ln in the soils with high sorption capacity is sorbed, and the increasing of doses leads to the decrease of the yield. The light lantanides are characterized by physical and chemical properties equal to Cа2+. And the mass replacement of Cа2+ by lantanides harms the development of plants. The high doses of lantanides have a negative impact on the biochemical processes in plants. The competition with iron and phosphorus is stipulated by the close solubility of iron and lanthanum phosphates: the accumulation of La in plants tissues affects the content of P and Fe within them.